2018
DOI: 10.1007/s12265-018-9788-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cardiac S100A1 Expression Improves Recovery from Global Ischemia-Reperfusion Injury

Abstract: Gene-targeted therapy with the inotropic Ca2 + -sensor protein S100A1 rescues contractile function in post-ischemic heart failure and is being developed towards clinical trials. Its proven beneficial effect on cardiac metabolism and mitochondrial function suggests a cardioprotective effect of S100A1 in myocardial ischemia-reperfusion injury (IRI). Fivefold cardiomyocyte-specific S100A1 overexpressing, isolated rat hearts perfused in working mode were subjected to 28 min ischemia (37 °C) followed by 60 min repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Nuclear transcription factor FOXO was thought to be involved in neuronal apoptotic signal transduction induced by hypoxic ischemia in the developing brain [44]. Indeed, FOXO is also associated with ischemia-reperfusion injury in various tissues including the heart [45] and liver [46]. Only one study investigated the relationship between baicalin and FOXO activation, implicating treatment with baicalin influenced phosphorylation/acetylation of FoxO1 via PI3K/Akt by insulin in aged rats [46].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear transcription factor FOXO was thought to be involved in neuronal apoptotic signal transduction induced by hypoxic ischemia in the developing brain [44]. Indeed, FOXO is also associated with ischemia-reperfusion injury in various tissues including the heart [45] and liver [46]. Only one study investigated the relationship between baicalin and FOXO activation, implicating treatment with baicalin influenced phosphorylation/acetylation of FoxO1 via PI3K/Akt by insulin in aged rats [46].…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 Jungi et al. 22 reported that S100A1 could exert a cardioprotective effect on global ischemia-reperfusion injury. The present study showed that the serum concentration of S100A1 was significantly increased in patients with NSTE-ACS and was closely related to the short-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Some researchers have studied whether the S100A1 level can be used to diagnose acute myocardial ischemia, and they found that a longer duration of myocardial ischemia was associated with a higher level of serum S100A1. 20,21 Jungi et al 22 reported that S100A1 could exert a cardioprotective effect on global ischemia- reperfusion injury. The present study showed that the serum concentration of S100A1 was significantly increased in patients with NSTE-ACS and was closely related to the short-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…A transcriptional regulation study through bioinformatics revealed that four potential hypoxia-inducible factor-1 alpha (HIF-1 α )-binding motifs on the promoter of renalase (an enzyme elevated during MIRI that can metabolize catecholamine) are novel loci involved in cardioprotection against MIRI [112]. S100A1 [113] and S100A6 [11], members of the S100 family protein containing EF-hand and Ca 2+ -binding motifs, as well as Annexin-5 (a member of the Annexin family containing Ca 2+ -dependent phospholipid binding motifs) [12], might regulate several intrinsic apoptosis pathways involved in MIRI, generating a smaller infarct size and improving the systolic function of the left ventricle. Similarly, the innovative roles and action sites of several cardioprotective genes against MIRI associated with intracellular homeostasis and antiapoptosis have been signposted using bioinformatic methods, such as STAT3 [114], GSTP [115], SGLT1 [116], BCL2 [117], and SERCA2 [118].…”
Section: Genetics and Epigenetics Of Mirimentioning
confidence: 99%